2001
DOI: 10.1081/pln-100107601
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Fertilizer Phosphorus Requirements of Canola, Lupin, and Wheat

Abstract: Increases in yield due to applications of phosphorus (P) (0, 5, 10, 15, 20, and 40 kg P=ha) applied as single (ordinary) superphosphate were measured for canola (Brassica napus), lupin (Lupinus angustifolius) and wheat (Triticum aestivum) in a field experiment on a deep sandy soil near Esperance, south-western Australia (WA). There are no data comparing the P requirements of these species grown at the same time, which was done by determining the amount of P required to produce 90% of the maximum yield for ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 18 publications
4
19
1
Order By: Relevance
“…Oilseed rape requirements for P are reported to be as high as for the small grains wheat and barley in western Canada (Ukrainetz et al, 1975). More recently, canola (B. napus) edible oil seed response to P has been compared to spring wheat (Nuttall and Button, 1990;Brennan and Bolland, 2001;Brennan and Bolland, 2005;Bolland, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Oilseed rape requirements for P are reported to be as high as for the small grains wheat and barley in western Canada (Ukrainetz et al, 1975). More recently, canola (B. napus) edible oil seed response to P has been compared to spring wheat (Nuttall and Button, 1990;Brennan and Bolland, 2001;Brennan and Bolland, 2005;Bolland, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Lafond and Gan (9) reported that though seed placed P did not affect winter wheat stand, grain yield was increased. In spring canola, Brennan and Bolland (2) reported that yield increased as P rate increased. The objective of this experiment was to quantify the effect of N and P on winter canola survival and crop yield in the Great Plains.…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons of wheat, narrow-leaf lupin (L. angustifolius L.), canola (Brassica napus L.) and the pasture legume, subterranean clover (T. subterranean L.) indicate that the critical Prequirement of the narrow leaf lupin is marginally (10%; Brennan and Bolland 2001) or considerably greater (70%; Ozanne et al 1976;Bolland 1992) than the critical requirements of wheat and subterranean clover (Ozanne et al 1976). Wheat and subterranean clover, in turn, have critical P requirements that are 25%-60% larger than that of canola (Bolland 1997;Brennan and Bolland 2001;Brennan and Bolland 2009). Because the critical P rankings of these crops are reasonably consistent, it is likely that better (targeted) management of soil P-fertility can be achieved across cropping rotations than is practised currently.…”
Section: Pasture and Crop Varieties With Low P Requirementsmentioning
confidence: 98%